An Analysis of Mathematics Education Quality: Case Study of Adiyaman University - Suat Aşkın; Murat Ayan (Selçuk Üniversitesi Sosyal Bilimler Enstitüsü Dergisi)
There is no doubt that fast and intense changes in the communication technologies of the globalized world have dramatically influenced the educational instituions as well as other sectors. Increasing demand for lifelong learning have been shaping educational institutions and emerging information society structure. The changes affect educational instituions in the way of requiring to bring up more qualified people who can contribute to information production and use it creatively. The main subject in service sector is human. The offering of qualified service is possible through qualified workers. Qualified human resource is developed by vocational education. When we look through a wider perspective, the role of the educational opportunities provided in higher education institutions is an undeniable fact in terms of the provision of sustainability in service quality. The service offered to the students in universities should be designed and offered in a way to meet the expectations and needs of students. The atmosphere should be created for the students to attend to and adopt the courses and to take the information which is conveyed to them. The education which is offered in the level of student skill should contribute to their lives, increase their commitment to the university and the education to be offere in universities therefore should reach their aim. Just like in all other service sectors, the inseperable, abstract, heterogenic and varible features of services offered in universities create hardships for performing measurement in this issue. In this study, the measurement of the expectations of students in the university from mathematics education and the service quality percieved in this sense are performed. The main group is comprised of the students of Adıyaman University. The total university student number in the year when the poll is conducted in 2012 is 12.000. The sample volume for the poll is determined as 400 students and the poll is performed. During the prescreening, 84 survey forms belonging to the included working group were detected not to have been filled correctly and not included in the analysis stage. In this context, educational quality has become a priority for all educational institutions. Educational quality of higher education institutions is both an indicator of development and the most prioritized driving factor of related efforts. The expectations and satisfaction levels of the studenst who are the ‘customers’ of higher education institutions are examined in this study. This article is a study for determination and optimization of the mathematics education quality for students who are studying in Adıyaman University